(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
The authors of this article analyze essence and designation of the payment system "Platon", serially consider the arguments of pros and cons of possible increase in a rate pushed by warring parties and also offer other ways of solution of the disputable situation.